Collaborative Management Between School Principals and Committees in Improving the Quality of Education - Luluk Wijiati; Usfandi Haryaka; Widyatmike Gede Mulawarman; Laili Komariyah; Nurlaili Nurlaili; Azainil Azainil (Journal of Educational Sciences, 2026)
Collaboration between school principals and school committees plays an important role in strengthening school governance and improving educational quality. This study aimed to describe the collaborative management between the principal and the school committee at SD Negeri 009 Samarinda Ilir using the planning, organizing, actuating, and controlling (POAC) management framework. A qualitative case study approach was employed. Data were collected through interviews, observations, and documentation involving the principal, committee members, and teachers. The data were analyzed using the Miles and Huberman interactive model, while validity was ensured through source and technique triangulation. The findings show that collaboration was implemented through participatory planning, clear task distribution, joint implementation of school programs, and continuous monitoring and evaluation. This partnership enhanced school facilities, strengthened educational programs, increased community participation, and built greater parental trust in the school. The study concludes that effective collaboration between principals and school committees, supported by the POAC management approach, contributes significantly to improving the quality of education and promoting good school governance. These findings suggest that collaborative management can serve as a practical model for strengthening partnerships between schools and communities to support sustainable educational improvement in elementary schools.